LEARNING PHENOMENA IN MANUFACTURING AND ARTIFICIAL NEURAL NETWORK - Car, Miroslav (Journal of Information and Organizational Sciences, 2007)
In the industrially advanced countries, that are different from our ex and present countries, to learning phenomena has been dedicated a significant attention for the last 60 years. One of more basic reasons is multiple purposes of results. Until now, there have been applied various approaches, methods and procedures for empirical data approximation, and in this articles some possibilities of artificial neural network application are researched.